Migration and Violence: Lessons from Colombia for the Americas : A workshop of the Transatlantic Forum on Migration and Integration and the Refugee Research Network (TFMI) (2013)
“Th e conference, “Migration and Violence: Lessons from Colombia to the Americas” was held in Bogotá D.C., Colombia at the Pontificia Universidad Javeriana on June 29, 2012. Th e main objective of the conference was to develop inter-disciplinary academic research in Central America and Mexico regarding the relationship between violence, particularly narco-violence, and migration. Th e setting in Bogotá D.C. was deliberate as the participants discussed how lessons learned from Colombia’s experience with narco-induced migration could be leveraged for the benefi t of Central America and Mexico. With the participation of experts on international migration, government representatives, academics, and civil society, the conference highlighted research results and relevant intervention experience concerning this problem in Colombia, El Salvador, Guatemala, and Mexico”--Introduction.